Implementation of Civics Education Learning on the Topic of Respecting Cultural and Religious Differences in Daily Life for 6th Grade Elementary/Islamic Elementary School Students. - Farida Catur Wahyu Anggriyani; Sugianor; Farhan (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
Citizenship Education (PKN) in elementary schools has an important role in shaping students' character as citizens who have social awareness and tolerance for cultural and religious differences. This article examines the implementation of PKN learning material "Respecting Cultural and Religious Differences in Everyday Life" in Elementary/MI Class 6, with a focus on effective teaching methods, challenges faced, and the impact on student attitudes and behavior. The research results show that PKN learning can increase students' understanding of the importance of respecting differences, even though there are several challenges related to limited teaching materials and social conditions in the surrounding environment. Through a contextual and interactive approach, the values of tolerance can be taught effectively and applied in students' daily lives.